2023
DOI: 10.3389/fpsyg.2023.1139687
|View full text |Cite
|
Sign up to set email alerts
|

The implicit preference evaluation for the ceramic tiles with different visual features: Evidence from an event-related potential study

Abstract: BackgroundCeramic tiles are popular because of their various forms, and they are often used to decorate the environment. However, few studies have applied objective methods to explore the implicit preference and visual attention of people toward ceramic tile features. Using event-related potential technology can provide neurophysiological evidence for the study and applications of tiles.Materials and methodsThis study explored the influence of pattern, lightness, and color system factors of ceramic tiles on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 72 publications
1
2
0
Order By: Relevance
“…The N200 component reflects a preferential selection of attention towards stimulusrelated attributes, while also revealing differences in emotional stimuli [100,101]. Moreover, compared to stimuli with a high preference, those with a low preference have been found to evoke a greater N200 amplitude [82,83,96]. The ERP results are consistent with the aforementioned studies, demonstrating that participants exhibit a higher N200 amplitude in response to low-preference APA as opposed to FPA with a higher preference.…”
Section: Neural Mechanisms Of Aesthetic Perception In Public Artsupporting
confidence: 83%
See 1 more Smart Citation
“…The N200 component reflects a preferential selection of attention towards stimulusrelated attributes, while also revealing differences in emotional stimuli [100,101]. Moreover, compared to stimuli with a high preference, those with a low preference have been found to evoke a greater N200 amplitude [82,83,96]. The ERP results are consistent with the aforementioned studies, demonstrating that participants exhibit a higher N200 amplitude in response to low-preference APA as opposed to FPA with a higher preference.…”
Section: Neural Mechanisms Of Aesthetic Perception In Public Artsupporting
confidence: 83%
“…Moreover, the N100 is also connected to the allocation of attention in aesthetic preferences. For instance, Chen et al [96] discovered that lighter tiles with higher preference scores could induce a larger N100 amplitude compared to darker tiles with lower preference scores. However, differing from the above studies, our statistical results demonstrate that the art's characteristic types did not induce a main effect on the frontal N100.…”
Section: Neural Mechanisms Of Aesthetic Perception In Public Artmentioning
confidence: 99%
“…Although physiological measurement methods have provided new perspectives and objective data for perception research, these technologies also face their own challenges and limitations. For example, research has shown that individual differences, such as age, gender, and body temperature, can affect the results of a galvanic skin response, making the comparison of GSR data across individuals complex [40,41]. Moreover, although an ECG can capture the physiological differences between positive and negative stimuli, it cannot effectively distinguish emotional changes occurring a few seconds before the stimulus appears [42].…”
Section: Previous Research Methods and Limitationsmentioning
confidence: 99%